Inprovement of Field Emission Properties of PBS Thin Films by Amorphous Carbon Coating - S. Jana; D. Banerjee; B. Kamaliya; K.K. Chattopadhyay (Журнал нано- та електронної фізики)
Lead sulfide (PbS) nanocrystalline thin films were synthesized at room temperature via chemical bath deposition on both silicon and glass substrates and coated with amorphous carbon of different thickness by varying deposition time in plasma enhanced chemical vapor deposition technique. The as prepared samples were characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and atomic force microscope (AFM). XRD study reveals that coating of amorphous carbon does not change the crystal structure of PbS. From FESEM images it is seen that the average size of PbS nanoparticle does not exceed 100 nm, though sometomes small cubic particles agglomerated to form bigger particles. The coating of amorphous carbon can be clearly visible by the FESEM as well as from AFM micrographs. Field emission study show a significant betterment for the carbon coated sample as compared to the pure PbS. The effect of inter-electrode distance on the field emission characteristics of best field emitting sample has been studied for three different inter-electrode distances.